Time-driven activity-based costing and room selling prices: A case study at The Sentra Hotel Manado - Kezia Brielni Wiltin Mewengkang; Agus Tony Poputra; Natalia Y. Telly Gerungai (Yayasan Widyantara Nawasena Raharja, 2026)
Time-Driven Activity-Based Costing (TDABC) is a refinement of Activity-Based Costing that uses time as the primary cost driver, allocating resource costs to activities in proportion to the estimated minutes each activity actually consumes. This study aims to (1) determine room selling prices at The Sentra Hotel Manado, a four-star hotel in North Sulawesi, using the TDABC method, and (2) compare the resulting prices with those currently set by hotel management under a cost-plus/dynamic-pricing approach, for all six room types over the full 2025 operating year. The Sentra Hotel Manado was selected as the case on the basis of data accessibility, management's willingness to disclose detailed cost records, and its representativeness of North Sulawesi's growing four-star hotel segment; as a single-case design, the findings describe this property's cost structure and are not intended to generalize numerically to other hotels. A case-study approach was used, drawing on observation, semi-structured interviews, and documentation, with room-service activity times measured through direct stopwatch timing cross-checked against staff interviews and standard operating procedures. The results show that TDABC-based room prices are as follows: Superior at Rp625,667; Deluxe at Rp753,386; Premier at Rp929,546; Suite at Rp1,167,762; Premier Suite at Rp2,518,164; and President Suite at Rp5,572,733. Management's cost-plus/dynamic-pricing prices for the same room types are Rp650,300; Rp785,100; Rp987,870; Rp1,215,500; Rp2,560,000; and Rp5,685,000, respectively. TDABC-based prices are consistently lower than management's prices, by 1.6% to 5.9% depending on room type, because time-proportional allocation captures differences in service intensity across room types more precisely than management's single, uniform 70% margin. The findings support a resource-consumption rationale for time-based costing in hospitality: allocating shared service resources by actual activity time, rather than by an aggregate markup, more closely reflects each room type's true resource consumption.